2014
DOI: 10.1128/aac.02579-13
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Placebo-Controlled, Single-Ascending-Dose Study of BMS-791325, a Hepatitis C Virus (HCV) NS5B Polymerase Inhibitor, in HCV Genotype 1 Infection

Abstract: f BMS-791325 is a nonnucleoside inhibitor of hepatitis C virus (HCV) NS5B polymerase with low-nanomolar potency against genotypes 1a (50% effective concentration [EC 50 ], 3 nM) and 1b (EC 50 , 7 nM) in vitro. BMS-791325 safety, pharmacokinetics, and antiviral activity were evaluated in a double-blind, placebo-controlled, single-ascending-dose study in 24 patients (interferon naive and experienced) with chronic HCV genotype 1 infection, randomized (5:1) to receive a single dose of BMS-791325 (100, 300, 600, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…To evaluate the ability of the compound to eradicate HCV RNA from GT3 to -6 chimeric replicon cells, replicon clearance studies were performed using BMS-791325 at a 300 nM concentration for up to 10 days. Since BMS-791325 has demonstrated substantial antiviral effect against GT1 patients in the clinic (28), GT1a replicon cells were used as a control, and a 300 nM concentration was chosen as it is the average minimum concentration of drug (C min ) observed at 24 h after a single 100-mg dose of BMS-791325 which resulted in a mean HCV RNA decline of approximately 1.3 log 10 copies/ml in HCV GT1-infected patients (28). Consistent with the EC 50 results, replicon clearance occurred efficiently in GT3a, -4a, and -5a chimeric replicons, similar to that observed in the GT1a replicon (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate the ability of the compound to eradicate HCV RNA from GT3 to -6 chimeric replicon cells, replicon clearance studies were performed using BMS-791325 at a 300 nM concentration for up to 10 days. Since BMS-791325 has demonstrated substantial antiviral effect against GT1 patients in the clinic (28), GT1a replicon cells were used as a control, and a 300 nM concentration was chosen as it is the average minimum concentration of drug (C min ) observed at 24 h after a single 100-mg dose of BMS-791325 which resulted in a mean HCV RNA decline of approximately 1.3 log 10 copies/ml in HCV GT1-infected patients (28). Consistent with the EC 50 results, replicon clearance occurred efficiently in GT3a, -4a, and -5a chimeric replicons, similar to that observed in the GT1a replicon (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…BMS-791325 was synthesized at Bristol-Myers Squibb. Daclatasvir (DCV; NS5A replication complex inhibitor) and asunaprevir (ASV; NS3 protease inhibitor) were previously described (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39).…”
Section: Cell Lines and Hcv Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of the P495L variant is ϳ2-fold lower than WT and is highly resistant to BMS-791325 inhibition (EC 50 Ͼ500 nM and IC 50 431 Ϯ 110 nM; Table 2) (10, 11). It was observed in replicons after selection in vitro and in clinical specimens of GT-1 patients treated with BMS-791325 (7,11). The P495L and L30S variants were used in this study to confirm that the inhibition and binding observed with WT NS5B is specific and to probe the impact of the weakened interaction between the thumb and finger on the inhibitor-enzyme interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The two-step binding mode and long residence time for BMS-791325 and WT NS5B may contribute to the efficacy that has been observed in vivo (7,46,47).…”
mentioning
confidence: 99%